Efficacy of Adding Midazolam to Bupivacaine for Transversus Abdominis Plane Block on Postoperative Analgesia after Hysterectomy: A Randomized Controlled Study - El Kenany, Samah (Anesth Essays Res, 2019)
BACKGROUND AND AIM: Different adjuncts have been utilized to promote the quality and prolong the duration of local anesthetics for a variety of regional block techniques. This study aimed to assess the effects of midazolam coadministered with bupivacaine in transversus abdominis plane (TAP) block on the 24-h morphine consumption, the postoperative analgesia duration and adverse effects. SETTINGS AND DESIGN: A prospective, randomized, controlled double-blind trial that was carried out at a university hospital. PATIENTS AND METHODS: Eighty-two females subjected to open total abdominal hysterectomy under general anesthesia were involved in this trial. Participants were allocated randomly to either of two groups (41 each). Control group: received TAP block with 20 mL of 0.25% bupivacaine or midazolam group: received TAP block using the same volume of bupivacaine plus 50 μg/kg midazolam/side. Postoperative cumulative 24-h morphine consumption, analgesia duration, pain score, sedation score, and adverse events were recorded. STATISTICAL ANALYSIS: Student's t-test, Mann–Whitney U-test, and Chi-square test were used. RESULTS: Patients in the midazolam group had a lower cumulative 24-h morphine consumption [median doses (interquartile range): 15 (10–19.50) mg compared to 25 (17.50–37) mg, P < 0.001], lower postoperative pain score at rest at the 4(th), 6(th), and 12(th) h (P = 0.01, 0.02, and 0.02, respectively) and on movement at 2, 4, 6, and 12 h (P < 0.001), longer time till the first postoperative demand for rescue analgesia (430.11 ± 63.02 min) compared to 327.78 ± 61.99 min (P < 0.001), and less sedation, nausea and/or vomiting, and pruritus. CONCLUSIONS: Adding midazolam as a bupivacaine adjuvant for TAP block reduces the 24-h morphine consumption, extends the postoperative analgesia duration, and decreases the incidence of adverse effects following abdominal hysterectomy.